The Forced Oscillation Technique in Paediatric Respiratory Practice. (March 2016) - Skylogianni, Eleni; Douros, Konstantinos; Anthracopoulos, Michael B.; Fouzas, Sotirios
Summary: The Forced Oscillation Technique (FOT) is a lung function modality based on the application of an external oscillatory signal in order to determine the mechanical response of the respiratory system. The method is in principal noninvasive and requires minimal patient cooperation, which makes it suitable for use in young paediatric patients. The FOT has been successfully applied in various paediatric respiratory disorders, such as asthma, cystic fibrosis, and chronic lung disease of prematurity, in order to assess airway obstruction, bronchodilator response, and airway responsiveness after bronchoprovocation challenge. This technique may be more sensitive than spirometry in identifying disturbances of peripheral airways and assessing the level of asthma control or the effectiveness of therapy at the long term. Further research is required to determine the exact role of the FOT in paediatric lung function testing and to incorporate the method in specific diagnostic and management algorithms.